2020
DOI: 10.18089/tms.2020.160405
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluating tourism experiences in senior mobility: an application of the OEC framework

Abstract: This research was developed in the frame of the VOLTO JÁ Project, which aims to implement a senior social exchange program in Portugal, among social economy organizations to promote tourism experiences for the elderly. The main goal of the research is to present a three-stage model of designing and evaluating tourism experiences in senior mobility, named as the OEC Model. This model was established based on a set of data collection instruments, which were chosen according to the goals of each stage of the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Interviews conducted with representatives of the tourism industry and local authorities revealed that key among the significant problems negatively influencing the size of the senior tourism market in European remote regions mentioned by the respondents are the difficulties in reaching seniors with tourist offers through the inadequate promotion of tourist packages targeted at the elderly. This is supported by the results of another study conducted by Amaral et al (2020), according to which it is very important to consider appropriate tools for promoting tourist offers targeted at seniors.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Interviews conducted with representatives of the tourism industry and local authorities revealed that key among the significant problems negatively influencing the size of the senior tourism market in European remote regions mentioned by the respondents are the difficulties in reaching seniors with tourist offers through the inadequate promotion of tourist packages targeted at the elderly. This is supported by the results of another study conducted by Amaral et al (2020), according to which it is very important to consider appropriate tools for promoting tourist offers targeted at seniors.…”
Section: Discussionmentioning
confidence: 72%
“…The elderly tourist segment in the new panorama of social and business management can undoubtedly be taken as a growing and constantly evolving sector, and much research has been undertaken to unravel its specificities (Amaral et al 2020). According to Le Serre (2008), the senior tourist segment represents a profitable source of revenue for companies linked to the tourism sector, not only because of its growing size, but also due to the availability of seniors and their time to travel.…”
Section: Elderly Tourists Segmentmentioning
confidence: 99%
“…It is necessary to create a specific tourist offer for this target customer group, which would be specially adapted to the elderly population, recognising both their socio-demographic characteristics and their future expectations [ 3 ]. Therefore, it is important that the available tourism products and destinations are adapted to the growing needs of current and future senior tourists, allowing for their disabilities and thus making it more accessible and elderly consumer friendly by addressing their specific needs [ 1 , 3 , 12 , 13 , 15 , 16 , 17 ].…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
“…At the same time, they are now more critical of the (tourist) industry due to their extensive experience in tourism acquired in their active age [ 15 ]. Therefore, to identify senior tourists except for the age [ 4 ], it is also necessary to consider their consumer behaviour, given their physical and mental condition [ 13 ].…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation